1998
DOI: 10.1103/revmodphys.70.1393
|View full text |Cite
|
Sign up to set email alerts
|

Astrometry and geodesy with radio interferometry: experiments, models, results

Abstract: Interferometry at radio frequencies between Earth-based receivers separated by intercontinental distances has made significant contributions to astrometry and geophysics during the past three decades. Analyses of such very long baseline interferometric (VLBI) experiments now permit measurements of relative positions of points on the Earth's surface and of angles between celestial objects at levels of better than one cm and one nanoradian, respectively. The relative angular positions of extragalactic radio sour… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
183
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(190 citation statements)
references
References 170 publications
0
183
0
3
Order By: Relevance
“…In geodetic/astrometric analysis (e.g. Sovers et al 1998;Schuh & Böhm 2013), the group delay τ is the main observable, defined as the difference in signal arrival time at the two antennas of a baseline. This delay is determined in the correlation process, as a combination of the measurements recorded in multiple frequency channels.…”
Section: S I M U L At I O N M E T H O Dmentioning
confidence: 99%
See 1 more Smart Citation
“…In geodetic/astrometric analysis (e.g. Sovers et al 1998;Schuh & Böhm 2013), the group delay τ is the main observable, defined as the difference in signal arrival time at the two antennas of a baseline. This delay is determined in the correlation process, as a combination of the measurements recorded in multiple frequency channels.…”
Section: S I M U L At I O N M E T H O Dmentioning
confidence: 99%
“…Besides contributing to the overall error budget of VLBI measurements as a systematic delay depending on the relative orientation of the source and the VLBI baseline (e.g. Sovers, Fanselow & Jacobs 1998), a temporal change in the brightness distribution of a source might also result in an apparent motion of this source (Ma et al 1998). Fey & Charlot (1997) showed that the size of the source structure (as, for example, determined by the SI) correlates with both the ICRF position accuracy and also with the magnitude of observed time variations in the source coordinates.…”
Section: Introductionmentioning
confidence: 99%
“…VLBI can also be used to create and improve ionosphere models and validate tropospheric parameters derived from other space geodetic techniques (Schuh & Behrend, 2012). It also furnish information about relativistic bending (Sovers et al, 1998), gravitational deflection of radio waves, rudimentary details of radio-source structure, Earth's long term motion in inertial space (galactic rotation) or Love numbers (Krasna, 2013). Therefore it is required to maintain all technical and computational aspects of the technique at the highest possible level (Petrachenko et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…During a geodetic VLBI session, a network of several radio telescopes observes a number of extragalactic radio sources to achieve interferometric measurements [e.g. Sovers et al (1998)]. The radio telescopes are located far away from each other, often on different tectonic plates, and thus form very long baselines.…”
Section: Introductionmentioning
confidence: 99%